Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 1 + 3 + 5 + 7 + ... + (2x - 1) = 225
(2x - 1 + 1) . [(2x - 1 - 1) : 2 + 1] : 2 = 225
2x.[(2x - 2) : 2 + 1] : 2 = 225
x . (x - 1 + 1) = 225
x . x = 225
=> x = 15
a,45 + x = 2x e, 4x + 3x = 70
\(\Rightarrow2x-x=45\) \(\Rightarrow7x=70\)
\(\Rightarrow x=45\) \(\Rightarrow x=10\)
Vậy x = 45 Vậy x = 10
b, 2 + x - 4 = 12 f, 6x - 18 = 0
\(\Rightarrow2+x=12+4\) \(\Rightarrow6x=18\)
\(\Rightarrow2+x=16\) \(\Rightarrow x=3\)
\(\Rightarrow x=14\) Vậy x = 3
Vậy x = 14 g, 72x : 36 = 2
c, 10 + x = 5 + 2x \(\Rightarrow72x=72\)
\(\Rightarrow2x+x=10+5\) \(\Rightarrow x=1\)
\(\Rightarrow3x=15\) Vậy x = 1
\(\Rightarrow x=5\) h, 13 + x = 5 + 2x
Vậy x = 5 \(\Rightarrow2x+x=13+5\)
d, 42 - 2x = 12 \(\Rightarrow3x=18\)
\(\Rightarrow2x=42-12\) \(\Rightarrow x=6\)
\(\Rightarrow2x=30\) Vậy x = 6
\(\Rightarrow x=15\)
Vậy x = 15
45 + x = 2x
x =45
2 + x - 4 =12
x - 2 = 12
x = 14
10 +x = 5 + 2x
-x = -5
x = 5
42 - 2x = 12
-2x = -30
x = 15
4x + 3x = 70
7x = 70
x = 10
6x - 18 = 0
6x = 18
x = 3
72x : 36 = 2
72x = 72
x = 1
13 +x = 5 +2x
-x = -8
x = 8
học tốt
126-2.(x-1)=20 120+3.(x-3)=180
2.(x-1)=126-20 3.(x-3)=180-120
2.(x-1)=106 3.(x-3)=60
x-1=106:2 x-3=60:3
x-1=53 x-3=20
x=53+1 x=20+3
x=54 x=23
a) -45:5(-3-2x)=3
5(-3-2x)=-45:3
5(-3-2x)=-15
-3-2x=-15:5
-3-2x=-3
2x=(-3)-(-3)
2x=-6
x=-6:2
x=-3
a ) x = 1 ; x = 0
b ) x = 1 ; x = 0
c ) x không có ; x không tồn tại
d ) x không có ; x không tồn tại
\(2x\left(x-5\right)-2x+10=0\)
\(2x^2-10x-2x+10=0\)
\(2x^2-12x+10=0\)
\(2\left(x^2-6x+5\right)=0\)
\(2\left(x-5\right)\left(x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=5\left(tm\right)\\x=1\left(tm\right)\end{cases};2=0\left(vonghiem\right)}\)
Ta có: 2x.(x-5) - 2x + 10 = 0
=> 2x.( x-5) - 2.(x - 5) = 0
=> (2x - x) (x-5) = 0
=> hoặc 2x-x = 0
hoặc x- 5 = 0
=> hoặc x = 0
hoặc x = 5
Vậy x = 0 hoặc x=5